P0467THE DIRECT USE OF ORAL ANTI-COAGULANTS IN MEMBRANOUS NEPHROPATHY. (6th June 2020) - Wills, Maximilian; Gupta, Sanjana; Gage, Alice; Ashman, Neil; Forbes, Suzanne
Abstract: Background and Aims: Barts Health has a dedicated membranous nephropathy (MN) service with 15-20 incident cases per year. Nephrotic syndrome secondary to MN in particular is associated with arterial and venous thrombosis. There is little evidence to guide optimum pharmacological prophylaxis. In those considered high risk, options include warfarin, heparin or aspirin. The advent of direct oral anti-coagulants (DOACs) offers an alternative, though evidence of efficacy is isolated to case studies. All patients with an albumin <25g/L are offered anticoagulation. We describe our use of DOACs in a large single centre MN cohort. Method: Retrospective data MN patients between 2015-2019 was analysed. This included: demographics; frequency, type and timing of thromboembolic and bleeding events; biochemical data at initiation and cessation of agent. Results: Total number of patients: 26 DOAC treatment courses: 30 Exposure to drug (patient days): 9899 Malignancy was excluded in all cases, with the exception of 1 case of MN secondary to cancer. There were 3 thromboembolic events in 3 patients; all events occurred on rivaroxaban and in PLA2Rab positive MN. Thrombotic events were all arterial, with no venous events, 2 cerebral artery infarcts and 1 lower limb arterial thrombosis. These patient's mean initial presentation PLA2Rab titres were 164 Kunits/L (75-248) and all were nephrotic at the time of the thromboembolic event. Events were 29, 128 and 340 days post DOAC initiation. 2 of these patients had a venous thrombosis prior to DOAC initiation. Event rate: 0.11 per patient year Safety data also demonstrated 3 bleeds in this patient cohort - all were minor as per ISTH criteria. 2 epistaxes and 1 associated with rectal prolapse, all without a haemoglobin drop. Conclusion: Our experience is that DOACs are safe and effective in patients with MN and offer a viable anti-coagulant alternative.